The phenotypic and genetic diversity test of several inbred lines on the 7th generation of melon (Cucumis melo) - HERI KUSTANTO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Kustanto H. 2023. The phenotypic and genetic diversity test of several inbred lines on the 7th generation of melon (Cucumis melo). Biodiversitas 24: 2623-2629. The needs for melon (Cucumis melo L.) keep increasing year by year. Some efforts to increase the quality of melon have been carried out to obtain better quality and quantity through plant breeding programs. Providing new melon inbred lines with different phenotypic and genotypic traits is very important in assembling melon hybrid varieties with new genetic characteristics, potentially production superior melon varieties. The study’s objective was to find out the genetic diversity of the tested melon genotypes and to obtain inbred lines of melon, which are the potential to be developed as superior hybrid varieties. The inbred lines of melons showed that the diversity coefficient values of morphological traits ranged from 0.57 to 1.0. There are 3 Groups, namely Group I, II, and III. Group I comprises two genotypes: MJ 34 and HHX 015. Group II is divided into 2, Group A and B. Gaboup A comprises three genotypes: MJ 25, Amanda variety as the standard of comparison, and MO 29, while Group B has one genotype: HHA 02. Group III comprises three genotypes: MSO 12, MSP 13, and HHAL 01. The traits are as follows: leaf length, leaf width, fruit length, fruit diameter, and the fruit flesh thickness have closely related to yield per plant.